Advances in management accounting. Vol. 19 - Lee, John Y.; Epstein, Mark (Emerald, 2011)
Featured in Volume 19 are articles on a call for future research on management accounting service quality; budget ratcheting and performance; effect of trust-in-superior and trustfulness on budgetary slack; relationship between purposes of budget use and budgetary slack; selection bias and endogeneity issues on the relationship between IT and firm performance; strategic budgeting in public schools; using a management accounting perspective to evaluate the production of future accounting professionals; the links between management control approaches and performance measurement systems; antecedents and consequences of cost.
Keywords: Business & Economics -- Accounting -- General.; Business & Economics -- Accounting -- Managerial.; Accounting.; Management accounting & bookkeeping.; Managerial accounting.; elektronické knihy; electronic books